(untitled) (Journal of the Bangladesh Agricultural University, 2010)
Naked neck fowl (Gallus gallus domesticus) comprises one of the indigenous chicken populations in Bangladesh. The present investigation was conducted to study the polymorphic pattern of the estrase isozyme in different tissues of the fowl by polyacrylamide gel electrophoresis (PAGE) system. In this experiment, α-napthyle and β-napthyle acetate were used as substrate. Esterase variability of different samples of fore brain, mid brain, hind brain, heart brain, liver, testis, oesophagus, gizzard, bile ducts, proventiculus, small intestine, large intestine pectoral muscle, pelvic muscle, lung, eye, kidney, pancreas, body muscle and blood cells were examined. Altogether four esterase bands were observed and the bands were designated as Esterase Est-1 2.0, Est-21.0 Est-30.75 and Est-40.15. Among the four bands Est-1 was the fastest and placed near to anode (+) electrode. Esterase showed tissue specific variation. Est-2 was found in almost all tissues, whereas Est-1 was observed only in liver. Est-3 and Est-4 were expressed exclusively in the nervous system especially in brain. Such findings may provide basic information to analyze the esterase activity in different tissues. Keywords: Esterase; Isozyme; Naked neck fowl; Tissue DOI: 10.3329/jbau.v8i1.6398 J. Bangladesh Agril. Univ. 8(1): 51-55, 2010